Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on the Republic of Korea reviews near-term economic prospects and risks. Korea experiences solid growth with low inflation, and vulnerabilities to potential shocks appear low. With Korea aging at an almost unprecedented rate, spending on pensions, health, and long-term care could rise by as much as 11 percent of GDP over the long term, threatening fiscal sustainability. Although risks facing financial institutions appear quite manageable, the authorities have focused on risks to the highly indebted household sector.